(untitled) (Research, Society and Development, 2023)
Antimicrobials are one of the best discoveries of the 20th century, which concomitant with their use came one of the biggest current problems in the world, bacterial resistance. Within this context, the present study aims to highlight the role of the pharmacist in the face of bacterial resistance and rational use of antimicrobials in the hospital environment. For the development of the study, a literature review was carried out for a reflective analysis based on studies published from 2010 to 2022 in the main databases found in Portuguese, English and Spanish. We selected 20 articles out of 6,650 found before applying the inclusion and exclusion criteria and performing the analysis. The clinical pharmacist plays a key role in combating bacterial resistance. In addition, the hospital environment is a place where there are more people in the same environment administering various antibiotics and different spectrums. The pharmaceutical professional has a direct and indirect impact on patients and medicines, being responsible for promoting the rational use of antibiotics, with standardization of medicines and possible interventions in the treatment, providing care, insurance, and health to the patient. Therefore, it is an important key in combating bacterial resistance, which is a public health issue, in addition to the possibility of promoting research and innovation in the field of microbiology and antimicrobial therapy.